Comparison of chloroquine, pyrimethamine and sulfadoxine, and chlorproguanil and dapsone as treatment for falciparum malaria in pregnant and non-pregnant women, Kakamega District, Kenya. - Keuter, M (1990)
OBJECTIVE--To compare treatment and protection against falciparum malaria in pregnant and non-pregnant women with three drug regimens. DESIGN--Prospective intervention study with six weeks' follow up. Patients received one of three drug regimens in order of entry. SETTING--Primary care hospital and secondary girls' school in rural western Kenya. PATIENTS--158 of 988 pregnant women (89 primigravid and 69 multigravid) in the third trimester and 105 of 1488 non-pregnant schoolgirls of reproductive age were parasitaemic (more than 500 asexual forms/microliter. These women were divided into three treatment groups by gravid state. INTERVENTIONS--Women were treated with chloroquine base 25 mg/kg over three days or pyrimethamine 75 mg and sulfadoxine 1500 mg as a single dose or chlorproguanil 1.2 mg/kg and dapsone 2.4 mg/kg as a single dose. MAIN OUTCOME MEASURES--Parasitaemia and haemoglobin concentrations measured at seven day intervals for six weeks. RESULTS--Primigravid women were more likely to be parasitaemic on follow up than multigravidas or nulligravidas, whose response was about the same. Parasites did not clear by day 7 in primigravidas in six (20%) of 30 who received chloroquine, three (8%) of 35 treated with pyrimethamine and sulfadoxine, and none of 23 treated with chlorproguanil and dapsone. At day 28, 83%, 19%, and 67% of primigravidas in these treatment groups were parasitaemic. Haemoglobin concentrations rose in all women, but improvement was sustained only in women who remained free of parasites. CONCLUSIONS--Clearance of parasites was better with either pyrimethamine and sulfadoxine or chlorproguanil and dapsone than with chloroquine. Longest protection was obtained with pyrimethamine and sulfadoxine.